2017
DOI: 10.1002/2017wr021051
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing and quantifying the crossover from capillary fingering to viscous fingering in a rough fracture

Abstract: Immiscible fluid‐fluid displacement in permeable media is important in many subsurface processes, including enhanced oil recovery and geological CO2 sequestration. Controlled by capillary and viscous forces, displacement patterns of one fluid displacing another more viscous one exhibit capillary and viscous fingering, and crossover between the two. Although extensive studies investigated viscous and capillary fingering in porous media, a few studies focused on the crossover in rough fractures, and how viscous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
89
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 85 publications
(146 reference statements)
14
89
2
Order By: Relevance
“…Furthermore, this trend implies that the leading edge of the CO 2 front advancing further downstream is not necessarily associated with the same finger but can instead alternate between fingers at different spatial locations as front advancement is more closely tied to local pore flow in the capillary fingering regime. Thus, these results reveal distinct pore‐scale invasion mechanisms for capillary and viscous fingering and are in agreement with previous experimental studies in rough fractures (Chen et al, ; Hu et al, ) and LBM simulations of flow in 3‐D porous rock media (Tsuji et al, ; Yamabe et al, ). For reference, x lead / L = 1 signifies the breakthrough of the CO 2 phase at the end of the porous section of the micromodel.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, this trend implies that the leading edge of the CO 2 front advancing further downstream is not necessarily associated with the same finger but can instead alternate between fingers at different spatial locations as front advancement is more closely tied to local pore flow in the capillary fingering regime. Thus, these results reveal distinct pore‐scale invasion mechanisms for capillary and viscous fingering and are in agreement with previous experimental studies in rough fractures (Chen et al, ; Hu et al, ) and LBM simulations of flow in 3‐D porous rock media (Tsuji et al, ; Yamabe et al, ). For reference, x lead / L = 1 signifies the breakthrough of the CO 2 phase at the end of the porous section of the micromodel.…”
Section: Resultssupporting
confidence: 92%
“…Wang et al () studied the crossover for supercritical CO 2 displacing water ( logM=1.25) in a homogeneous micromodel over a Ca range of 7.61logCa4.73 and noted a substantial decrease in CO 2 saturation at logCa=5.91 and −5.21, which is consistent with the findings of Lenormand et al (). Chen et al () investigated the crossover during water displacing oil ( logM=3,2.7,2,1.7) in a hydrophobic rough fracture for 7.07logCa3.07 and observed that the saturation of the invading fluid first decreased and then increased with increasing Ca , with the minimum value occurring at logCa=4.07 or logCa=5.07, depending on M . The existence of a minimum value was attributed to the fact that both fingering propagation toward the outlet and void filling in the transverse/backward directions were suppressed during crossover.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the immiscible two‐phase flow regime gradually deviates from IP (Figure a) with increasing Ca and nonwetting phase saturation (Figures b and c). This transitional behavior of increasing S n with Ca was suggested in recent experimental observations (Chen et al, ) and earlier theoretical work (Lenormand et al, ) when a low‐viscosity fluid displaces a viscous fluid. It also agrees well with previous numerical results (Yang et al, ) showing that increasing Ca will yield a relatively higher S n during the primary drainage process when viscosities of the two phases are identical.…”
Section: Resultssupporting
confidence: 69%
“…That is, with increasing capillary number, Ca = μu /γ , where u is mean velocity, viscous forces gradually become more important but still less significant than capillary forces. Since u = b 2 /(12 μ )·Δ P / L , and since in our simulations the maximum Δ P = ~1.4 × 10 3 Pa, L = 1 m, and < b > =5 × 10 −5 m, which therefore result in a maximum Ca = ~9.72 × 10 −6 , capillary forces fairly dominate over viscous forces (Chen et al, ). Consequently, the immiscible two‐phase flow regime gradually deviates from IP (Figure a) with increasing Ca and nonwetting phase saturation (Figures b and c).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation